Evaluation of radiological health risk due to ingestion and inhalation of radon in commercial packaged fruit juices consumed in Turkey. - Jamasali, Yusof-den; Turhan, Şeref; Bakır, Temel K.; Altuner, Ergin. M.; Duran, Celalattin; Hançerlioğulları, Aybaba; Kurnaz, Aslı (International Journal of Environmental Health Research, 2024)
Fruit juices (FJs) are among the most popular beverages frequently preferred by consumers, believing FJs contain the nutritional values, minerals, phytochemicals, vitamins, and antioxidants necessary for a healthy life. However, FJs may contain natural radionuclides such as radon (222Rn), which originates from the fruit and water utilized in their production, at levels that may pose a health risk to people. Inhalation and ingestion of 222Rn gas increases the risk of lung and stomach cancer. In this study, commercially packaged FJs from the seventeen most popular brands consumed in Turkey were analyzed for physicochemical properties and 222Rn activity concentrations to evaluate the radiological health risk. The values of pH, brix and 222Rn activity concentrations in FJ samples varied from 2.68 to 4.28, 2.50 to 14.30%, 9.6 ± 1.1 to 25.2 ± 2.5 mBq/L, respectively. The radiological health risk caused by internal exposure was evaluated for children and adults by estimating the ingestion and inhalation annual effective dose. The average values of the total annual effective dose for children and adults were found as 0.039 µSv and 0.056 µSv, respectively, which are much lower than the recommended dose of 100 µSv for drinking water.